On Asian Clivinini. Revision of the westwoodi-species group of the genus Clivina Latreille, 1802 (Coleoptera, Carabidae, Clivinini) - Balkenohl, Michael (Zootaxa, 2025)
The Oriental Clivina westwoodi-species group is revised. In order to maintain stability of the nomenclature, lectotypes have been designated for C. wallacei wallacei Putzeys, C. westwoodi Putzeys, C. monticola Andrewes, and C. subdepressa Kult. Compendious descriptions or formal redescriptions are provided for C. monticola Andrewes, C. quadrataconvexa Balkenohl, C. depressa depressa Kult, C. subdepressa Kult, C. vigil Darlington, C. westwoodi Putzeys, C. wallacei wallacei Putzeys, C. wallacei philippinensis Kult, and C. integra Andrewes. The following 26 new taxa are described: C. collaricrenata sp. nov., C. convexaquadrata sp. nov., C. trapezicollaris sp. nov., C. tuberculifer sp. nov., C. depressa samarensis ssp. nov., C. bilobata sp. nov., C. caputdepressa sp. nov., C. opacielytra sp. nov., C. bauri sp. nov., C. dilutureticulata sp. nov., C. gracilicollis sp. nov., C. depressiforma sp. nov., C. geiseri sp. nov., C. passimpunctata sp. nov., C. hartmanni sp. nov., C. spatulifigura sp. nov., C. caputopaca sp. nov., C. circumreticulata sp. nov., C. circumopaca sp. nov., C. berndjaegeri sp. nov., C. wallacei solomonensis ssp. nov., C. punctaticollis sp. nov., C. paris sp. nov., C. similata sp. nov., and C. neglecta sp. nov. An identification key to the taxa of the C. westwoodi—species group is provided. All taxa are figured including male and female genitalia, if available. The available faunistic information is provided.